Comparison of Soil Organic Carbon Stocks Evolution in Two Olive Orchards with Different Planting Systems in Southern Spain - José A. Gómez; Lizardo Reyna-Bowen; Pilar Fernández Rebollo; María-Auxiliadora Soriano (Agriculture, 2022)
This study presents an evaluation of soil organic carbon (SOC) and stock (SOCstock) for the whole rooting depth (60 cm), spaced 55 months in two adjacent olive orchards with similar conditions but different tree densities: (i) intensive, planted in 1996 at 310 tree ha−1; (ii) superintensive, planted in 2000 at 1850 tree ha−1. This was carried out to test the hypothesis that olive orchards at different plant densities will have different rates of accumulation of SOC in the whole soil rooting depth. SOC increased significantly in the superintensive orchard during the 55-month period, from 1.1 to 1.6% in the lane area, and from 1.2 to 1.7% in the tree area (average 0–60 cm), with a significant increase in SOCstock from 4.7 to 6.1 kg m−2. In the intensive orchard, there was not a significant increase in SOCstock in 0–60 cm, average of 4.06 and 4.16 kg m−2 in 2013 and 2018, respectively. Results indicate a potential for a significant increase in SOC and SOCstock in olive orchards at higher tree densities when combined with temporary cover crops and mulch of chopped pruning residues. The increase is associated with an increase in SOC, mainly at a 0–15 cm depth. Results also point to the need for improve our monitoring capabilities to detect moderate increases in SOC.